Introducing the Tactics and Resources Dataset: Resources, Sponsors and Escalation of Non-state Actors - Tom Konzack (Peace Economics, Peace Science and Public Policy, 2026)
Abstract To cut through inconsistent findings on non-state violence born of contested concepts and uneven data, I introduce the Tactics and Resources Dataset (TRD): a panel dataset on 649 violent and non-violent political non-state organisations. It focuses on their tactical choices and the types and origins of resources provided to them, alongside political, social, and economic indicators and key historical junctures. TRD offers a robust empirical foundation for studying how various types of resources and external sponsors influence escalation trajectories, why some actors transition into violence while others maintain restraint, and how tactics are interrelated. Another distinctive feature is its explicit modelling of the constituent country, in addition to home and target country. First empirical findings demonstrate the analytical value of the dataset, emphasising the crucial role of resources and sponsors in non-state actors’ escalation dynamics.